Evaluation of the membrane damage mechanism of protocatechualdehyde against Yersinia enterocolitica and simulation of growth inhibition in pork. (30th November 2021) - Tian, Lu; Wang, Xuyang; Zhang, Di; Wu, Mi; Xue, Zhifei; Liu, Zhiqiang; Yang, Siqi; Li, Hui; Gong, Guoli
Highlights: The antimicrobial mechanism of protocatechualdehyde was described. Cell dysfunction were characterized using fluorescent probes. Protocatechualdehyde causes morphological changes in Yersinia enterocolitica. Protocatechualdehyde controls the contamination of Yersinia enterocolitica in pork. Abstract: This study sought to explore the antibacterial mechanism associated with membrane damage in Yersinia enterocolitica by protocatechualdehyde (PCA), thus providing improved knowledge of whether PCA is suitable for pork preservation. The minimum inhibitory concentration (MIC) of PCA was determined by micro-broth dilution. We then characterized functional and morphological changes of Y. enterocolitica treated with PCA. Finally, the growth inhibition model of PCA against Y. enterocolitica in pork was established using the response surface method. Accordingly, the MIC of PCA against Y. enterocolitica was found to be 0.3125 mg/mL. Significant observations incorporated membrane depolarization, a markedly decreased intracellular ATP and pH, and morphological changes induced by PCA treatment. After PCA treatment under low temperatures, the average Y. enterocolitica count in pork decreased by two log cycles. According to the obtained findings, PCA exhibited satisfactory performances as a food preservative to control the growth and reproduction of Y. enterocolitica in pork.